(untitled) (Revista Electrónica REDINE, 2018)
In this essay raises some reflections on Dysfunctional Family and its influence on school performance of children between 6 and 13 years old, in this regard it should be noted that the problems facing any family, is reflected by all members and especially children who manifest this distortion in school performance, which ranges from behavioral disorders of thought, feeling, hyperactivity and attention deficit. When these events occur, the teacher must establish an intervention and appropriate guidance to parents first, and this situation is not successful, then it becomes necessary to guide these parents to resort to other professionals who can provide appropriate help. The basic idea of this research is that the Dysfunctional Families recognize their problems and then seek solutions encouraging